Hypoxia in A Patient with Anti-p200 Pemphigoid under Combined Dapsone and Pantoprazole Treatment - Lang, Sebastian; Saenger, Philipp Wilhelm; Kocina, Sandra; Von Loeffelholz, Christian (Biomedicines, 2022)
A 70-year-old male patient was admitted to our dermatology outpatient clinic with newly developed personality changes and signs of hypoxemia. His anti-p200 Pemphigoid was treated with Dapsone for a few weeks. Due to generalized tonic-clonic seizure with a subsequent Glasgow Coma Scale of 5 points and a peripheral oxygen saturation not exceeding 88% under conditions of high-flow nasal cannula, he was intubated by the emergency team and transferred to the intensive care unit. Comprehensive tests were performed, but Dapsone-induced methemoglobinemia remained the exclusive explanation for the observed scenario, although arterial MetHb analysis showed a peak value of only 6%. The patient recovered shortly after repeated infusions of Methylene blue and Ascorbate, and cessation of Dapsone. We provide an overview of the pathophysiology, diagnostic procedures, and possible explanations for this case of Dapsone-induced methaemoglobinaemia. In conclusion, our case report provides evidence that even mild chronic methemglobinemia can induce severe clinical symptoms.
CRIS-Team Scopus Importer:2022-11-25
Keywords: CYP2C19; CYP2C9; G6PD-deficiency; hemolysis; NAFLD; proton pump inhibitors; sepsis